2013
DOI: 10.1530/erc-13-0444
|View full text |Cite
|
Sign up to set email alerts
|

Support of a bi-faceted role of estrogen receptor β (ERβ) in ERα-positive breast cancer cells

Abstract: Expression of estrogen receptor alpha (ERα) in breast cancer identifies patients most likely to respond to endocrine treatment. The second estrogen receptor, ERβ, is also expressed in breast tumors, but its function and therapeutic potential needs further study. Whereas in vitro studies have established that ERβ opposes transcriptional and proliferative functions of ERα, several clinical studies report its correlation to proliferative markers and poorer prognosis. The data demonstrating that ERβ opposes ERα ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 98 publications
(138 reference statements)
3
34
0
1
Order By: Relevance
“…This is particularly in the context of Castrate Resistant Prostate Cancer (CRPC) where it has been proposed as a driver of androgen receptor (AR)-dependent gene transcription (Yang et al., 2012, Yang et al., 2015), along with a potential role in mediating the transition from hormone-sensitive to CRPC (Zellweger et al., 2013). In breast cancer, it has been suggested that ERβ may have a ‘bi-faceted role’ and should not simply be considered a tumor-suppressor (Jonsson et al., 2014). ERβ has been reported to ‘cross-talk’ with androgen receptor-positive breast cancer (Rizza et al., 2014) and may be an important factor in ERα-negative breast cancer (Gruvberger-Saal et al., 2007, Smart et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly in the context of Castrate Resistant Prostate Cancer (CRPC) where it has been proposed as a driver of androgen receptor (AR)-dependent gene transcription (Yang et al., 2012, Yang et al., 2015), along with a potential role in mediating the transition from hormone-sensitive to CRPC (Zellweger et al., 2013). In breast cancer, it has been suggested that ERβ may have a ‘bi-faceted role’ and should not simply be considered a tumor-suppressor (Jonsson et al., 2014). ERβ has been reported to ‘cross-talk’ with androgen receptor-positive breast cancer (Rizza et al., 2014) and may be an important factor in ERα-negative breast cancer (Gruvberger-Saal et al., 2007, Smart et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both are nuclear receptors, which dimerize and translocate to the nucleus after ligand binding and regulate transcription of target genes through binding to estrogen-response elements in the DNA [2530]. The receptors can further interact with other transcription factor complexes, such as activating protein-1 (AP1), stimulating protein 1 (Sp1), and nuclear factor-κB (NFκB) in a process called transcription factor crosstalk [31–35].…”
Section: Estrogen Receptor Beta (Erβ) Has a Role In Crcmentioning
confidence: 99%
“…Controversy surrounds the clinical importance of ERβ in breast cancer, as patient survival for proliferative mammary tumor or ovarian cancers have been more closely correlated with ERα . However, some studies have demonstrated that ERβ exhibits both anti‐proliferative and proliferative properties, suggesting a bi‐faceted role for ERβ . ERβ expression has been correlated with the proliferation marker Ki67 in primary breast tumors .…”
Section: Divergent Role For Erβ In Tumorigenesismentioning
confidence: 99%
“…ERβ expression has been correlated with the proliferation marker Ki67 in primary breast tumors . In ERβ‐overexpressed breast cancer cell lines, it was shown that constitutively expressed ERβ did not reduce cell proliferation in T47D cells; on the contrary, the constitutively expressed ERβ increased cell proliferation in MCF7 cells . Furthermore, ERβ expression correlated with a higher risk of relapse in node‐positive breast cancer patients, indicating a more aggressive clinical course .…”
Section: Divergent Role For Erβ In Tumorigenesismentioning
confidence: 99%